Activated protein C levels and outcome in patients with cardiogenic shock complicating acute myocardial infarction. Issue 4 (1st June 2017) - Fellner, Barbara; Rohla, Miklos; Jarai, Rudolf; Smetana, Peter; Freynhofer, Matthias K; Egger, Florian; Zorn, Gerlinde; Weiss, Thomas W; Huber, Kurt; Geppert, Alexander
Abstract: Introduction: In patients with severe sepsis, low levels of activated protein C are associated with high morbidity and mortality. In an observational study we investigated whether patients with cardiogenic shock have decreased circulatory levels of activated protein C, and if these are associated with increased mortality. Methods: We measured serum activated protein C and interleukin-6 levels in 43 patients with cardiogenic shock following acute myocardial infarction and in 15 control patients with uncomplicated myocardial infarction at days 0–5 and 7 after the onset of shock/myocardial infarction. Results: Activated protein C levels were significantly lower in patients with cardiogenic shock compared to controls. In cardiogenic shock patients, there was no difference in activated protein C levels at baseline, whereas activated protein C levels significantly declined in 28-day non-survivors at day 2, compared with 28-day survivors. Lower levels of activated protein C were associated with a higher degree of vasopressor need, whereas there was no significant association with multiple organ failure in the first days. Regarding the inflammatory response, a strong inverse correlation was observed between interleukin-6 and activated protein C levels. Conclusion: Patients with cardiogenic shock who did not survive up to 28 days showed a decline in activated protein C levels during the course of the disease, which was inversely correlated with interleukin-6. This study underlines sustained inflammatory mechanisms in the development and persistence of cardiogenic shock, highlighting a potential effect of anti-inflammatory interventions early during cardiogenic shock.